Discussion of gastroesophageal reflux disease issue in World gastroenterological congress abstracts (Shanghai, 2013) - V. O. Kaybysheva; A. S. Trukhmanov; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To demonstrate most pressing issues of diagnostics and treatment of gastroesophageal reflux disease (GERD), presented in abstracts of the World gastroenterological congress (China, 2013).Key points. Following tendencies and advances deserve the highest attention: wide introduction of new diagnostics methods of GERD in the last years, e.g.: рН-impedance measurement and high resolution manometry, development of new method of non-invasive GERD diagnostics at primary healthcare stage - GERD Q questionnaire, optimization of GERD treatment and its complications.